Financing New Zealand Superannuation - Brian McCulloch; Jane Frances (New Zealand Government, The Treasury, 2001)
The New Zealand Superannuation Fund is being established as a means of smoothing out the impact on the rest of the Crown's finances of the transition that will take place over the next fifty years to a permanently higher proportion of the population being eligible for New Zealand Superannuation, the universal pension paid to New Zealanders over the age of 65. This paper discusses the financial issues surrounding the determination of the contributions that the Government would be required to make to the Fund over time in order to meet this objective. The calculation of the required contribution rate is derived as a function of future expected entitlement payments, future expected nominal GDP, future expected investment returns, and the Fund balance. Estimation issues are discussed and the implications of volatility in investment returns are examined. Some issues in assessing long-term expected returns are addressed in an appendix.
Keywords: C23; G1; H55; 330; pension fund; capital markets; investment returns; social security; retirement income